2022
DOI: 10.3390/nu14163424
|View full text |Cite
|
Sign up to set email alerts
|

Reversing Type 2 Diabetes in a Primary Care-Anchored eHealth Lifestyle Coaching Programme in Denmark: A Randomised Controlled Trial

Abstract: The goal of this trial was to investigate whether an eHealth lifestyle coaching programme led to significant weight loss and decreased Haemoglobin A1c (HbA1c) in patients with type 2 diabetes. In an RCT, 170 patients were enrolled from 2018 to 2019 for intervention or control. Inclusion criteria were diagnosed with type 2 diabetes, BMI 30–45 kg/m2, and aged 18–70 years. Exclusion criteria were lacks internet access, pregnant or planning a pregnancy, or has a serious disease. Primary and secondary outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(73 reference statements)
2
14
0
Order By: Relevance
“…These results are expected to be clinically relevant for patients with T2D when weight loss is sustained for more than two years. 22 Moreover, these findings support that using telehealth 23 lifestyle coaching has comparable remission rates with other more intensive resource-heavy weight-reducing strategies in patients with T2D and probably also for other chronic conditions with overweight as an important issue. 2,3 The importance of the empathic relationship between the person living with obesity and the health care professional delivering the coaching is known from traditional motivational interviewing 24 and previous qualitative studies suggest that this is equally important when using a combination of face-to-face consultations and a collaborative telehealth tool.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These results are expected to be clinically relevant for patients with T2D when weight loss is sustained for more than two years. 22 Moreover, these findings support that using telehealth 23 lifestyle coaching has comparable remission rates with other more intensive resource-heavy weight-reducing strategies in patients with T2D and probably also for other chronic conditions with overweight as an important issue. 2,3 The importance of the empathic relationship between the person living with obesity and the health care professional delivering the coaching is known from traditional motivational interviewing 24 and previous qualitative studies suggest that this is equally important when using a combination of face-to-face consultations and a collaborative telehealth tool.…”
Section: Discussionmentioning
confidence: 71%
“…These results are expected to be clinically relevant for patients with T2D when weight loss is sustained for more than two years. 22 Moreover, these findings support that using telehealth 23 lifestyle coaching has comparable remission rates with other more intensive resource-heavy weight-reducing strategies in patients with T2D and probably also for other chronic conditions with overweight as an important issue. 2,3…”
Section: Discussionmentioning
confidence: 71%
“…Service prices, health insurance policies and health management privacy also affect social and policy‐related resource access (Ben‐Assuli, 2022; Huter et al, 2022). Christensen et al (2022) showed that an electronic health guidance regimen combined with basic health resources can significantly reduce body weight and HbA1c in patients with T2DM. Based on this study, diabetes‐related medical resources played a key role in telenursing implementation, but patients also play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Ladner et al (2022) showed that diabetes telenursing has more potential in rural areas. Studies have shown that (Christensen et al, 2022;Crowley et al, 2022;Iversen et al, 2020;Sjöström et al, 2021;Zhang et al, 2022) telenursing for diabetes can improve blood sugar control (Goh et al, 2021), induce behavioural changes, reduce hospitalization and prevent complications, thereby improving at-home diabetic self-management (María Gómez et al, 2022).The implementation of self-management behaviours requires access to disease-related social support resources, including but not limited to family, friends, medical professionals and reliable information sources (Glasgow et al, 2000). In reality, telenursing is the telematics-based remote implementation of in-person care services (Al-Badri et al, 2022), which by its very nature still depends on actual nursing resources (Anderson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nine study interventions were delivered in 3 months or less 17,18,30,31,[33][34][35][36]43 and 10 interventions lasted 5-6 months. [22][23][24][25]28,29,32,[40][41][42] Seven study interventions were 1 year long, 16,20,21,26,37,38,44 and three interventions were longer than 1 year. 19,27,39 Most studies evaluated the effects of DHC up until the end of the intervention while 31% of studies continued to conduct follow-ups post-inte rvention, 16,21,25,29,[34][35][36][41][42][43] with the furthest follow-up occurring 17-months post-intervention.…”
Section: Implementation and Maintenancementioning
confidence: 99%